Supporting graduate employability from generalist disciplines through employer and private institution collaboration : final report 2015. - Kinash, Shelley; Crane, Linda (Australia. Office for Learning and Teaching, 2015)
This project addressed how educators and employers can best support graduate employability. Employability means that higher education institutions and employers have supported knowledge, skills and attributes leading to career success for graduates. The focus is on generalist disciplines including visual/performing arts, life sciences, humanities and computer science. The aims of this project (commissioned in December 2013) were to: (1) achieve a greater clarity on the issues, challenges and contexts of graduate employability; (2) identify and review the strategies that have been successfully used to address these challenges; (3) create opportunities for the diverse stakeholder groups to share their perspectives; and (4) promote strategies that may be used by the various stakeholders to collaborate on improving graduate outcomes. The overall findings of this project were that: (a) there is evidence of gaps between the perspectives of students, graduates, employers and higher education personnel in how to approach the overall higher education experience for heightened employability; (b) multiple stakeholders stated that the most employable graduates are those who have a broad-based experience, and are able to sell their own personal identity, brand and profile; (c) transferable skills and a broad-based student experience are more important than the particular discipline of study for impacting employability; (d) higher education personnel (private and public) believe they can bolster graduate employability by promoting/supporting extra-curricular and co-curricular activities and skill development (technical and transferable) through work experience, internships and placements and other types of employability strategies; (e) students have a variety of needs, resources and capacities, such that extra-curricular and co-curricular activities and experiences may not be realistic and accessible to all; and (f) there are barriers to employment, such as gender, ethnicity and socioeconomic background that may override employability strategies and supports. [Executive summary, ed]